Pembuatan Mesin Pneumatic Power Forging Hammer Untuk Meningkatkan Produktifitas Pandai Besi Tradisional Di Aceh Barat - Herri Darsan; Herdi Susanto; Murhaban Murhaban; Rita Fazlina; Zammiq Syari; Al Munawir; Teuku Farizal (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2021)
Forging is a metal processing process by changing its shape in a hot state with a punch system. Some of the forging products produced by the blacksmith industry such as machetes, knives, hoes, dodos, household, agricultural, and equipment for agricultural and plantation products. But now the existence of the blacksmith industry has begun to fade because of the proliferation of manufactured products. The traditional blacksmith business that was pioneered in the village of Blang Berdang, Johan Pahlawan District, West Aceh Regency, Pande Besi UDM Service. Regency. West Aceh. which has been passed on to the third generation which is managed from generation to generation to get the iron processing skills obtained from his parents. the use of this tool to facilitate the community in the productivity of blacksmiths technologically in West Aceh. The results of iron forging can increase marketing and promotion for their work so that the product can be accepted by traditional and modern markets. From the description above, it is necessary to manufacture a Pneumatic Power Forging Hammer Machine to Increase the Productivity of Traditional Blacksmiths in West Aceh and assistance in Product Promotion so that their products can be sold throughout Indonesia.